Military intervention in pre-war Japanese politics : Admiral Kato Kanji and the 'Washington system' - Gow, I. T. M. (Curzon, 2004)
A study of the impact of inter-war naval arms control policy-making on the domestic politics of Japan, especially the areas of civil-military, inter-military (Army/Navy) and especially intra-military (navy) relations.